The Effect of Work Ethic and Work Discipline on Employee Performance Through Work-Life Balance Policies at The Sirnajaya Village Office - Sri Wahyuningsih; Catur Sasi Kirono (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to analyze the influence of work enthusiasm and work discipline on employee performance, by considering the mediating role of work-life balance policies at the Sirnajaya Village Office. The novelty of this research lies in its integration of work-life balance as a mediating factor between motivation, discipline, and performance an approach that remains underexplored in public sector organizations at the village level. A quantitative approach was employed, involving 94 respondents selected from a population of 123 employees using Slovin’s formula with a 5% margin of error. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with LISREL version 8.8. The results indicate that both work enthusiasm and discipline have a significant positive impact on employee performance. Enthusiasm also positively affects work-life balance, while discipline shows a negative relationship with it. Furthermore, work-life balance was found to partially mediate the relationship between the independent variables and performance. The study is limited to a single village office with a relatively small sample size, which may restrict broader generalization. Nonetheless, the findings highlight the importance of balancing motivation and discipline through supportive work-life balance policies to enhance sustainable employee performance.